Pediatric Critical Care Perceptions on Analgesia, Sedation, and Delirium - Smith, Heidi A. B.; Berutti, Tyler; Brink, Emily; Strohler, Bradly; Fuchs, D. Catherine; Ely, E. Wesley; Pandharipande, Pratik P. (Seminars in Respiratory and Critical Care Medicine, 2013)
Critically ill children suffer from pain and anxiety additionally in the face of severe organ dysfunction. The critical care environment challenges pediatric patients' emotional and developmental capabilities. Disease-focused therapy is a priority and usually requires separation of patient from family and completion of invasive procedures. With the lack of familiar surroundings, inability to self-soothe, and deficiency of sleep, critically ill children may benefit from a multidisciplinary approach to care with a specific goal of pain management. Due to the challenges unique to critical care of children, sedatives and hypnotics are heavily relied upon to “protect” children from the intensive care experience. Delirium occurs in at least 30% of critically ill infants and children reported in small prospective studies, without a large-scale protocol for delirium monitoring. Adult studies demonstrate an overwhelming prevalence of delirium in the critically ill, associated with significant morbidity and mortality. Recently, the diagnosis of pediatric delirium has been enhanced by the validation of bedside tools that encourage monitoring within the critical care setting. Though there are likely many similarities in delirium among adults and children, there is much to learn in regard to unique risk factors and outcomes for children. Perhaps, considering the neurodevelopmental and psychosocial capacities of a child, a creative approach to assess and control pain and anxiety, while optimizing disease-related therapies, may ultimately minimize the risk for the development of delirium or other long-term complications of critical illness.
Keywords: brain dysfunction; confusion; delirium; encephalopathy; pediatric; critical care; sedation; pain; analgesia; anxiety; agitation